Non-transport roles of nuclear import receptors: In need of the right balance - Damizia, Michela; Altieri, Ludovica; Lavia, Patrizia (Frontiers in Cell and Developmental Biology, 2022)
Nuclear import receptors ensure the recognition and transport of proteins across the nuclear envelope into the nucleus. In addition, as diverse processes as mitosis, post-translational modifications at mitotic exit, ciliogenesis, and phase separation, all share a common need for regulation by nuclear import receptors - particularly importin beta-1 and importin beta-2/transportin - independent on nuclear import. In particular, i) nuclear import receptors regulate the mitotic spindle after nuclear envelope breakdown, ii) they shield cargoes from unscheduled ubiquitination, regulating their timely proteolysis; iii) they regulate ciliary factors, crucial to cell communications and tissue architecture during development; and iv) they prevent phase separation of toxic proteins aggregates in neurons. The balance of nuclear import receptors to cargoes is critical in all these processes, albeit in opposite directions: overexpression of import receptors, as often found in cancer, inhibits cargoes and impairs downstream processes, motivating the therapeutic design of specific inhibitors. On the contrary, elevated expression is beneficial in neuronal contexts, where nuclear import receptors are regarded as potential therapeutic tools in counteracting the formation of aggregates that may cause neurodegeneration. This paradox demonstrates the amplitude of nuclear import receptors-dependent functions in different contexts and adds complexity in considering their therapeutic implications.